Vascular tumors - Bueno, Lady (Cirugía del Uruguay, 1973)
Vascular sarcomas have their origín in mesenchymatose angioforming cells. According to Cassinelli they should be termed "angiosarcomas", while Stout describes two histological forms depending on whether proliferated element is endothelial (malign hemangioendothelioma) or is related to Zimmermann's pericytes (hemangiopericytoma). In the former, tumoral cells are inside the vascular basal and in the latter, outside. They are infiltrating tumors which cause metastasis mainly through the bloodstream. Lymphangiosarcomas are exceptional tumors and the only cases described are related to chronic post-mastectomy lymphoedema.